2016
DOI: 10.1016/s1470-2045(16)30561-7
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib, cabozantinib, or erlotinib plus cabozantinib as second-line or third-line treatment of patients with EGFR wild-type advanced non-small-cell lung cancer (ECOG-ACRIN 1512): a randomised, controlled, open-label, multicentre, phase 2 trial

Abstract: Summary Background Erlotinib is approved for the treatment of all patients with advanced non-small cell lung cancer (NSCLC), but is most active in the treatment of EGFR mutant NSCLC. Cabozantinib, a small molecule tyrosine kinase inhibitor, targets MET, VEGFR, RET, ROS1, and AXL, which are implicated in lung cancer tumorigenesis. We tested the efficacy of cabozantinib and the combination of erlotinib plus cabozantinib, as compared with erlotinib, in patients with EGFR wild-type NSCLC. Methods In this three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 26 publications
1
92
0
1
Order By: Relevance
“…Recently, data from the ecog 1512 randomized phase ii trial comparing erlotinib alone, cabozantinib alone, and the combination erlotinib-cabozantinib in patients with previously treated egfr wild-type nsclc were published 47 . Greater efficacy was seen in both groups of patients treated with cabozantinib.…”
Section: Other Antiangiogenic Agents Not Approved In Nsclcmentioning
confidence: 99%
“…Recently, data from the ecog 1512 randomized phase ii trial comparing erlotinib alone, cabozantinib alone, and the combination erlotinib-cabozantinib in patients with previously treated egfr wild-type nsclc were published 47 . Greater efficacy was seen in both groups of patients treated with cabozantinib.…”
Section: Other Antiangiogenic Agents Not Approved In Nsclcmentioning
confidence: 99%
“…To date, inhibitors of HGF/c‐Met signaling have been developed as monotherapies or combination therapies with EGFR‐TKI for the treatment of NSCLC (eg cabozantinib, Exelixis; crizotinib, Pfizer; tivantinib, ArQule; onartuzumab, Roche; rilotumumab; Amgen; ABBV‐399, AbbVie). In lung cancer cells with c‐Met pathway‐induced resistance to EGFR inhibitors, combination of a c‐Met inhibitor and EGFR inhibitor has been shown to efficiently overcome such resistance …”
Section: Introductionmentioning
confidence: 99%
“…Using a cell line‐based model, we also found that dual inhibition of EGFR and AXL has the potential to overcome crizotinib resistance in vitro and in vivo. These findings could be clinically relevant, as EGFR inhibitors and AXL inhibitors have been approved for clinical use, and the efficacy and safety of combination therapy with cabozantinib and erlotinib have been reported in clinical trials …”
Section: Discussionmentioning
confidence: 99%